Population dynamics and genotypic richness of threatened Acropora species and their hybrid in the U.S. Virgin Islands - Hannah F. Nylander-Asplin; Ronald L. Hill; Jennifer C. Doerr; Lisa Greer; Nicole D. Fogarty (Coral Reefs, 2021)
Acropora cervicornis and A. palmata have experienced substantial losses in coral cover throughout the Caribbean, but their hybrid ( A. prolifera ) appears to be increasing at some sites. The shifts in relative abundance could result from hybridization with subsequent asexual fragmentation, recent increased hybridization, or a disproportionate loss in the parental species. Here, acroporid taxa from three U.S. Virgin Islands sites were genotyped revealing 35 hybrid genotypes, suggesting multiple hybridization events. Genotypic richness in A. cervicornis (0.62), A. prolifera (0.64), and A. palmata (0.68) was not significantly different across sites. To further explore acroporid dynamics at these sites, we analyzed existing photo transects from 2009 to 2017 to reveal significant losses of A. cervicornis but stable hybrid percent cover. High genotypic richness and stable populations suggest acroporid hybrids may become the primary shallow reef-builders in some locations previously occupied by the parental species.